L'expérience de Parcoursup des néo-bacheliers - Esther Geuring
Transforming the methods of access to higher education, Parcoursup strengthens the effect of secondary school and teachers in the guidance of final year students. Informed and supported, theses high school students are invited to reify their aspirations through non-hierarchical wishes. Borrowing from the sociology of experience (Dubet, 1994), this contribution questions the way in which high school students experienced this Parcoursup procedure which engages their orientation process. From a double survey carried out by questionnaire (n=713) and by interview (n=37) among first-year university students, the results show that if their experience of the procedure in its technical dimension is facilitated by the support received, the way they do understand the discourses of their teachers is more nuanced.